Do aging suits adequately simulate objective age-related decline in gait?: A kinematic comparison of induced aging in young and middle-aged adults - Gerhardy, Thomas; Schmidt, Laura; Wahl, Hans-Werner; Mombaur, Katja; Sloot, Lizeth H. (Educational gerontology, 2026)
Aging suits are widely used as arguably didactic tool to foster understanding for age-related challenges in healthcare training by mimicking physical impairments associated with aging. However, effects on functional levels are ambiguous and necessitating validation of their potential to simulate age-related walking impairments. We evaluated effects of wearing an aging suit on kinematic gait variables, in younger and middle-aged adults in different walking conditions. Available reference data were used to compare aging-suit induced effects to standard and dual-task walking in older adults. Whole-body kinematics (sagittal ankle-, knee-, hip-angles, arm-swing, trunk-bend) and spatiotemporal parameters (walking speed, stride length, step width) were measured in 14 young (20-34 years) and 15 middle-aged adults (40-63 years). SPM analysis and mixed ANOVA were conducted to evaluate the effects of the suit, age-group and their interaction. Overall, wearing the aging suit changed gait patterns, but kinematic parameters were hardly affected in both groups. During standard walking, arm-swing decreased by 17%, walking speed by 9%, and step width increased by 15% across both groups. Compared to reference data, changes in arm-swing corresponded to an instant aging effect of 45-55 years in young and 15-25 years in middle-aged adults. The aging suit changed gait patterns considerably making both groups walk more cautiously compared to reference values of older adults. However, performance deficits seen in individuals 80+ years were clearly not attained. Caution is advised when using aging suits as an educational tool to simulate age-related walking impairments.
Veröffentlicht online: 03 Mar 2025
Gesehen am 25.09.2025